2009
DOI: 10.1007/s10342-009-0340-0
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental phases in a temperate natural spruce-fir-beech forest: determination by a supervised classification method

Abstract: A sequentially shifting fine-scale mosaic of forest patches in different phases of development is widely accepted as being a basic description of the natural dynamics of temperate deciduous and mixed forests. The determination of these patches and phases has often been performed using subjective field observations and simplistic or loosely defined mapping criteria, with resulting maps being observer-dependent. The goal of this study is to develop a more objective, more complex and spatially explicit method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 40 publications
5
61
0
1
Order By: Relevance
“…Similar results were reported also by Zenner et al [37] from an Oriental beech virgin forest in northern Iran, where diameter distributions of all stages were reverse J-shaped, but with significant differences between the Optimal and Initial stage as well as the Initial and Decay stage. Unlike Král et al [36], who found the Optimal stage with a typical bell-shaped diameter distribution in a common beech-silver fir-Norway spruce stand, in NNR Dobročský prales the Optimal stage with homogenous stand structure was not present. The Optimal stage reached the highest values of growing stock and basal area that distinguished it from the other stages; however, the stand maintained the differentiated structure.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Similar results were reported also by Zenner et al [37] from an Oriental beech virgin forest in northern Iran, where diameter distributions of all stages were reverse J-shaped, but with significant differences between the Optimal and Initial stage as well as the Initial and Decay stage. Unlike Král et al [36], who found the Optimal stage with a typical bell-shaped diameter distribution in a common beech-silver fir-Norway spruce stand, in NNR Dobročský prales the Optimal stage with homogenous stand structure was not present. The Optimal stage reached the highest values of growing stock and basal area that distinguished it from the other stages; however, the stand maintained the differentiated structure.…”
Section: Discussionmentioning
confidence: 49%
“…In general, these characteristics influence the shape of diameter distribution [36] and result in different types of distribution for each development stage, i.e., right-skewed distribution for the Initial stage, unimodal symmetric distribution for the Optimal stage and bimodal distribution for the Decay stage. In NNR Dobročský prales, we observed some differences from this general pattern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the raster approach can fail to detect overlapping stages (Korpel, 1995;Drössler & Meyer, 2006), as shown by Grassi et al (2003). A more advanced mapping of developmental phases in a natural spruce-fir-beech forest was presented (Kral et al, 2010), which also included dead trees. In addition, irregular patches (usually 400 -1100 m² in size) with spatially distinct stand characteristics (tree number, standing volume, deadwood) were indicated by statistical models (Kral et al, 2014).…”
Section: Silvicultural Research In Natural Beech Forests In Europementioning
confidence: 99%